What is the best therapy for phantom limb pain?. Issue 11 (November 2015) - Over, Darrell R.; Douangkesone, Silakhone
Abstract : Evidence‐Based Answer : Morphine and gabapentin are effective for phantom limb pain, while amitriptyline and memantine afford no benefit (SOR: A, systematic review). Farabloc® limb cover does not significantly decrease phantom limb pain (SOR: B, RCT). Transcutaneous electrical nerve stimulation (TENS) and home‐based mirror therapy may be helpful (SOR: C, cohort studies).